Clinical Profile of Patients Admitted with Seizure Disorder in a Tertiary Care Hospital of Central Nepal - Bhandari, Isha; Malla, Kalpana Karmacharya; Ghimire, Pukar; Bhandari, Bibek (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Seizure is one of the common presentation and reason for hospital admission in children. This study aims to address the etiology and clinical characteristics of the patient. Methods: This was a descriptive, cross-sectional study in which children of age 1month to 15 years presenting with seizure were included. The data was analyzed using SPSS 16.0. Results: Out of 192 patients,126 (65.6%) were males and 66(65.6%) were females with the ratio of 1.9:1. Distribution of events in different age groups were 16.1%(n=31) in group of 1month to 1 years, 63%(n=121) in group of 1yrs to 5 years,12.1%(n=24) in group of 5years to 10 years and 8.3%(n=16)in children above 10years.70.3% had febrile seizure, with the highest incidence in age group of 1 to 5 years. Generalised tonic clonic seizure was seen in 94.3% and focal motor seizure in 5.7%. No difference was seen in distribution of the type of seizure across different age groups (p= 0.192).Presenting complaints were fever in 75.5%, loss of consciousness in 26.0%, vomiting in 25.0% , headache in 23.4%, altered sensorium in 8.3% and focal neurological deficits in 8.3%. 33.9% of children had a family history of seizure. Causes of febrile seizures included upper respiratory tract infection in 82.2%, acute gastroenteritis in 12.6%, urinary tract infection in 3% and pneumonia in 2.2%. Afebrile seizure was idiopathic in 38.6% and identifiable causes in the remaining were sequelae of birth asphyxia in 17.6%, hypoglycemia in 8.8%, neuronal migration defects and neurocysticercosis in 5.3%. No relation was observed between the history of perinatal asphyxia and the age of onset of seizure (p=0.250). Of all the patients 57.8% were discharged without antiepileptic, 27.6% were treated with monotherapy whereas 14.5% required polytherapy to achieve seizure control. Conclusions: Seizure is a common problem in children, with the highest incidence in the age group of 1 to 5 years and febrile seizure is the most common type of seizure in children.